The Relic - Queirós, Eça de, 1845-1900 (Book collections on Project MUSE., 2023)
"The Relic tells the story of an orphaned young man, Teodorico Raposo, who is brought to Lisbon from a provincial town in Portugal to live with his aunt, a rigid, stern - and oftentimes - forbidding Catholic. Her devout circle of acquaintances is made up almost entirely of priests, many of whom are more concerned with appearances than spirituality, and seeking her and their approval, Teodorico is driven to attend Mass, say rosaries, and frequent churches, all the while awakening to sensuality, women, and the material life in conflict with "Auntie's" devotions, which are - inwardly - devoid of the charity preached by Christ. When Teodorico obtains a degree from the University of Coimbra, Auntie sends him to the Holy Land to search for a relic to cure her ills. He meets up with a learned German author and, after a sojourn to Egypt, the two make their way to the land trod by Jesus. It is there that Teodorico has the dream that takes up nearly one third of the novel: he witnesses the travails that lead to the Passion and Crucifixion, as well as the aftermath of Christ's death. Faced now with his mission, Teodorico embarks on a search. He soon comes upon an item, a "true" relic authenticated by his German friend, the sanctity of which will send Auntie to the heights of spiritual bliss, so much so that she will make him her heir. But when Teodorico returns to Lisbon with it, deception awaits her as the result of a simple mistake that had been made, and disinheritance awaits him as a result of Auntie's anger and vindictiveness"--